Integrating Systems Thinking and Storytelling - Ollove, Maggie; Lteif, Diala (FormAkademisk, 2017)
This paper explores the role of design in conflict resolution when doing so means balancing burdened pasts with present uncertainties. To prove its relevance in today’s complex problem spaces, design cannot remain stagnant; it must evolve alongside the pace of development. Designing within complexity is unprecedented. Yet, design can define structures that guide an understanding of this complexity. The methodology and case study described in this paper explore how systems thinking, storytelling and grounded theory can contribute to this understanding. The methodology aims to combine subjective perspectives with systemic analyses to create a collective narrative that reveals the multitude of individual understandings of conflicts. Ultimately, this methodology does not attempt to resolve conflict; instead, it aims to provide an in-depth diagnosis of a wicked problem and question the role of design therein.